Timing matters: the processing of pitch relations - Weise, Annekathrin; Grimm, Sabine; Trujillo-Barreto, Nelson J.; Schröger, Erich (Frontiers in Human Neuroscience, 2014)
The human central auditory system can automatically extract abstract regularities from a variant auditory input. To this end, temporarily separated events need to be related. This study tested whether the timing between events, falling either within or outside the temporal window of integration (~350 ms), impacts the extraction of abstract feature relations. We utilized tone pairs for which tones within but not across pairs revealed a constant pitch relation (e.g. pitch of 2nd tone of a pair higher than pitch of 1st tone, while absolute pitch values varied across pairs). We measured the Mismatch Negativity (MMN; the brain’s error signal to auditory regularity violations) to 2nd tones that rarely violated the pitch relation (e.g. pitch of 2nd tone lower). A Short condition in which tone duration (90 ms) and stimulus onset asynchrony between the tones of a pair were short (110 ms) was compared to two conditions, where this onset asynchrony was long (510 ms). In the Long Gap condition the tone durations were identical to Short (90 ms), but the silent interval was prolonged by 400 ms. In Long Tone the duration of the first tone was prolonged by 400 ms, while the silent interval was comparable to Short (20 ms). Results show a frontocentral MMN of comparable amplitude in all conditions. Thus, abstract pitch relations can be extracted even when the within-pair timing exceeds the integration period. Source analyses indicate MMN generators in the supratemporal cortex. Interestingly, they were located more anterior in Long Gap than in Short and Long Tone. Moreover, frontal generator activity was found for Long Gap and Long Tone. Thus, the way in which the system automatically registers irregular abstract pitch relations depends on the timing of the events to be linked. Pending that the current MMN data mirror established abstract rule representations coding the regular pitch relation, neural processes building these templates vary with timing.